Improvement of kidney histological morphology in nephrotoxic paracetamol-induced rats by cassia alata treatment - Abu I.F.; Mat A.C.; Zulkifli M.; Juliana N.; Mohamad M.H.N. (J. K. Welfare and Pharmascope Foundation, 2024)
Indexed by Scopus